BS EN 4641-401. Aerospace series. Cables, optical 125 μm diameter cladding. Part 401. Tight structure bend insensitive 50 µm/125 µm GI fibre nominal, 1, 8 mm outside diameter. Product standard (22nd September 2022) - British Standards Institution,
No abstract available